Harnessing mobile devices to support the delivery of community-based clinical care: a participatory evaluation - Jasmine Harvey; John Powell (BMC Medical Informatics and Decision Making, 2019)
Abstract Background A large provider of community health services (an NHS Trust in England) deployed Apple iPads to its front-line community-based healthcare clinicians (predominantly nurses) to enable them to increase responsiveness to patients’ and their families’ needs. We conducted a participatory formative evaluation of this iPad initiative among different users and the informatics teams implementing it, to establish how such initiatives can sustain adoption and achieve their stated benefits. Methods We used a participatory approach involving a partnership between study investigators and key decision-makers of the initiative to engage stakeholders in the study. Methods included focus groups and group discussion, meetings with key personnel and analysis of documents related to the initiative. Using a participatory technique, members of the organisation identified practical challenges to inform the on-going process of implementation and adoption in the Trust. Results Healthcare professionals identified many benefits associated with having iPads to support care delivery, including streamlined workflows and accessible information at the point-of-care in the community. However, challenges that interfered with implementation were also reported by both the team implementing the initiative (IT team) and early users. Challenges reported by IT team are: adopter clinicians’ scepticism and suspicion; clinician non-compliance with training and operational guidance procedures; and managing adopter expectations. Challenges reported by users are: setting-up and maintaining the devices on a long-term basis; blurring of personal and professional boundaries; and disconnection from the IT team. Results show that these challenges could be overcome if there were more informal ‘socialised’ interactions between adopters and between adopters and the IT team. Conclusions We suggest that similar initiatives require increased ongoing dialogue between different levels of stakeholder groups, in the form of socialised engagements, to avoid common misunderstandings and to promote the processes involved in co-constructing the initiative on a generally-agreed and sustainable basis.